A social stakeholder support assessment of low-carbon transport policy based on multi-actor multi-criteria analysis: The case of Tianjin. (July 2015) - Sun, Hui; Zhang, Yiting; Wang, Yuning; Li, Lei; Sheng, Yun
Abstract: Based on multi-actor multi-criteria analysis (MAMCA), this paper evaluates the low-carbon transport policies in Tianjin, China. MAMCA is a methodology that is used to evaluate different policy measures by explicitly accounting for the opinions of various stakeholders. This paper refines the model based on social network analysis to measure the weights of stakeholder opinions and applies the model to the case of Tianjin. Six intervention low-carbon transport policies (tax adjustment, pricing adjustment mechanisms, multi-operation mechanisms, environmental propaganda, traffic demand management, and state funding and subsidies) are evaluated based on the aims and objectives of various stakeholders (government supervisory authorities, end users, infrastructure operators, infrastructure suppliers, academics, the traffic management sector, the technology division, and the planning department) using snowball sampling techniques. Overall, the results showed that the most supportive policies are traffic demand management and state funding and subsidies. The MAMCA also provided insights into the position and preferences of stakeholders in relation to the aims and objectives of low-carbon transport policy. As such, the results can assist decision makers in comparing, selecting and adjusting low-carbon transport policies as well as attracting support for policy implementation. Highlights: We used multi-actor multi-criteria analysis to study the preferences of various stakeholder groups with different objectives in relation to low-carbon transport policies in Tianjin, China. The highlights of the model is the refinement based on social network analysis to measure the weights of stakeholder opinions in multi-actor multi-criteria analysis. The analysis result provided insights into the position and preferences of stakeholders in relation to the aims and objectives of low-carbon transport policy.